NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM Q.S. AL-HUJURAT AYAT 13 (Analisis Double Movement Fazlur Rahman) - Jamaludin; Muhamad Slamet Yahya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
there are still many intolerance attitudes In Indonesian education. For example, PPIM UIN Jakarta's research produced, 30 percent of students in Indonesia have a low and very low religious tolerance. So that multicultural education is very important to note. Al-Qur'an as a guide for humans does not contain specific vocabulary about multicultural, but that indicates multicultural values, according to Sakho, there are 102 verses. One of them is Q.S. Al-Hujurat verse 13. So that this research has the aim of exploring multicultural education values contained in Q.S. Al Hujurat verse 13. This study is included in the literature research, namely by collecting data and information contained in the library space, magazines, and history of a story. Therefore, researchers used Fazlur Rahman's double movement theory to be used as a surgical analysis. Double Movement theory has 2 movements: first, moving from special (particular) to general; Secondly, movement from the general to the special one. Thus, this research concluded, that there are 4 multicultural education values: 1.) The value of equality; 2.) The value of brotherhood; 3.) The value of humanitarian; and 4.) The value of justice.